Implementation of Social Care Character Education in Islamic Elementary Schools: Implementasi Pendidikan Karakter Peduli Sosial di Sekolah Dasar Islam - Febriana, Dita Wahyu; Amrullah, Muhlasin (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the implementation of social care character education and its supporting and inhibiting factors at SDI Darul Hikmah Krian. The method used in this research is qualitative. The subjects of this study were the principal, homeroom teacher, homeroom teacher and students of SDI Darul Hikmah Krian. Collecting data in this study using interviews, observation and documentation. Checking the validity of the data using source triangulation and technical triangulation. The results of the study conclude that the implementation of social care character education in SDI Darul Hikmh Krian The authors of this study conclude that educating students in school classrooms involves three stages. The first is the Planning Phase, where the educator makes an educational plan. The second is the Learning Implementation Phase, where students implement the educational plan in their learning. The last stage is the Learning Evaluation Stage, where educators evaluate the effectiveness of learning implementation. In addition, teachers also use examples and habits to teach social care education to their students during class time